Tweede Oostvlaamse Kunstbiënnale : 4/10-13/10/85 - Baeyens, Martin; Schepens, Herman ([S.l.] : [s.n.], 1985)
Baeyens, Martin R. ; Bekaert, Piet ; Bilquin, Jean ; Brems, Walter ; Burssens, Jan ; De Blok, Luc ; De Buck, Siegfried ; De Clerck, Antoon ; De Clerck, Katelijn ; De Clercq, Rosita ; De Keyser, Raoul ; De Kramer, Enk ; De Mey, Jos ; De Rycke, Walter ; [et al.]
boek